2017
DOI: 10.13168/agg.2017.0010
|View full text |Cite
|
Sign up to set email alerts
|

Deriving common seasonal signals in GPS position time series: by using multichannel singular spectrum analysis

Abstract: We estimated the common seasonal signal (annual oscillation) included in the Global Positioning System (GPS) vertical position time series by using Multichannel Singular Spectrum Analysis (MSSA). We employed time series from 24 International GNSS Service (IGS) stations located in Europe which contributed to the newest ITRF2014 (International Terrestrial Reference Frame). The MSSA method has an advantage over the traditional modelling of seasonal signals by the Least-Squares Estimation (LSE) and Singular Spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Zhu et al (2016) used the MSSA approach to investigate the inter-annual oscillations in glacier mass change estimated from gravity recovery and climate experiment (GRACE) data in Central Asia. Gruszczynska et al (2017) compared the MSSA-, SSA-and least-squares estimationderived seasonal signals. They showed that the seasonal signals detected by MSSA are not affected by noise as much as the SSA-derived oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al (2016) used the MSSA approach to investigate the inter-annual oscillations in glacier mass change estimated from gravity recovery and climate experiment (GRACE) data in Central Asia. Gruszczynska et al (2017) compared the MSSA-, SSA-and least-squares estimationderived seasonal signals. They showed that the seasonal signals detected by MSSA are not affected by noise as much as the SSA-derived oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the basic capability of decomposition, SSA can be applied in gross errors detection, interpolation and denoising of gravity data (Guo et al 2018a, b;Yu et al 2018). The main calculation steps of SSA are given below according to the research of Golyandina and Zhigljavsky (2013).…”
Section: Singular Spectrum Analysismentioning
confidence: 99%
“…Selection of the proper window length depends on the problem in hand, and on preliminary information about the time series. In the general case no universal rules can be given for the selection of the window length (Golyandina et al 2001). But there is a recommendation that the windows length is generally chosen as the common multiple of the known periods (Kondrashov et al 2010;Wang et al 2019).…”
Section: Singular Spectrum Analysismentioning
confidence: 99%
“…Accordingly, this periodic signal is almost offset at annual speeds. Periodic signals arise under the influence of various factors (Dong et al, 2002;Gruszczynska et al, 2017;Tretyak et al, 2015). As periodic oscillations are practically constant, they do not appear at the average velocities of vertical movements determined on the basis of long-term data processing, but the accuracy of velocity determination is different.…”
Section: The Purpose and The Task Of The Researchmentioning
confidence: 99%